Psychophysiological peculiarities of adolescent athletes of different sports specialization - Vedernikova, E. V.; Morozova, M. A.; Shushkanova, E. G.; Krotova, M. N. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the psychophysiological characteristics of adolescent athletes of various sports specializations.